Militarismo civil y pactos de gobierno: rastreo de relaciones entre el Ejecutivo y la Fuerza Pública en El Salvador (1989-2023) - Augusto Rigoberto López Ramírez; Claudia Ivón Rivera-Andrade; Jorge Alberto Rodríguez-Ponce (Revista Criminalidad, 2026)
The article examines the evolution of the relationship between the Executive and the security forces in El Salvador from 1989 to 2023 using the process tracing methodological strategy. Based on the analysis of documentary sources, press notes, social media, and institutional speeches, the study reconstructs six phases in the shaping of these ties. The central argument holds that, over time, a political-institutional pact was consolidated that combines corporate benefits for security institutions with a greater capacity for political control by the Executive. This process reaches its critical point during Bukele's administration (AB), in which budget expansion, discursive legitimization, intensive use of the security forces, and partisan political loyalty converge, creating a pattern of civil militarism in the exercise of state power.